Genetic profile of domestic cat (Felis catus L.) population of Aoshima Island (Japan) - S. K. Kholin (Вавиловский журнал генетики и селекции)
The paper analyzes the genetic profile of the domestic cat population of the Aoshima Island. The population has been established in the middle of the last century, after a small group of animals was imported for rodent control. Based on three photographs, the genotypes of the cats in three overlapping groups (75, 56, and 70 individuals) were determined. The mutant allele frequencies of the sex-linked O (Orange) locus and the three autosomal loci a, W, and l (Agouti, White, and Long hair) responsible for coat color and length were estimated. The population lacks the mutant alleles d (Dilution locus), W and wg (White), tab (Tabby), TiA (Ticked) present in other populations of Japan. This is an almost monomorphic population with prevailing red and tortoiseshell individuals. Most cats have interrupted stripes (genotype Ti+Ti+TaM-). The island’s population differs from the other populations of the Japanese islands in the frequencies of two mutant alleles, O and a. The frequency of the O allele (q(O) = 0.580) is one of the highest in the region, while the frequency of the a allele (q(a) = 0.276) is two times lower than in the other populations. In both cases, the differences in frequencies between the neighbouring populations are significant (p < 0.0001). An independent study of the same population revealed a similar genetic structure. However, it detected the presence of the d allele, the frequency of the a allele was higher (0.534 versus 0.276, p < 0.020). The genetic profile, frequencies of mutant alleles in the population, and history of its origin indicate a significant influence of the founder effect on the genetic structure of the island’s domestic cat population.